Papillary thyroid carcinoma in ovarian strumal carcinoid tumor: case report - Ana Paula Percicote; Sérgio Bruno Bonatto Hatschbach; Sérgio Ossamu Ioshii; Tiago Jacometo Coelho de Castilho; João Augusto Bahr; Camila Gadens Zamboni (Sociedade Brasileira de Patologia Clínica, 2013)
Strumal carcinoid tumor is an uncommon type of ovarian teratoma containing thyroid and carcinoid tissue. We report the case of a 49 year-old patient with menstrual irregularity. The ultrasonographic imaging revealed a mass in the left ovary. The histopathological assessment showed a papillary thyroid carcinoma in a strumal carcinoid tumor.